A step too far? The European financial transactions tax on shadow banking. Issue 6 (2nd July 2016) - Gabor, Daniela
ABSTRACT: This paper focuses on the European Commission's proposals to include the repo market – a market systemic to European (shadow) banking – in the financial transactions tax (FTT). It asks why the FTT governments negotiating under the enhanced co-operation procedure quickly removed the repo market from the scope of the FTT. It argues that the European repo market, rather than a shadow market energized by regulatory arbitrage, as it is customary to portray it, grew out of a public–private joint venture before the crisis. Thus, regulators became deeply embedded – through their government bond markets and policy frameworks – in (repo) market-based finance. This convergence in public and private interests creates new trade-offs and ambiguous preferences that allow private finance to successfully mobilize resistance to reform, creating coalitions with public actors such as the European Central Bank.